TEKNIK-TEKNIK YANG DIGUNAKAN OLEH GURU PEMBIMBING DALAM MEMBANTU MENGATASI MASALAH PRIBADI PESERTA DIDIK BROKEN HOME MELALUI KONSELING PERORANGAN DI SMA NEGERI 11 PADANG - Sari, Novita; Kasih, Fitria; Nita, Rahma wira (Bimbingan dan Konseling, 2013)
Problems that occur in learnersâ selves who come from a broken home among adolescents from time to time tend to increase, both qualitatively and quantitatively. The problem in this research is: How do the techniques used by a teacher counselor in helping broken home learnersâ problem through personal counseling in SMA 11 Padang. The purpose of this study was to determine how far of the techniques used by the teacher counselor in helping students broken home in overcoming their problems through personal counseling. This research was a descriptive research; it was describe of things as it is. The population of this study was a broken home students, the number of the students was 43 students. This study used total sampling technique that taken sample from the entire population because fewer than 100 people. The instrument used in this study was a questionnaire. Meanwhile, for analyzing the data the researcher used percentages technique. The results of this study showed that (1) Teacher efforts in expressing their students in very well category with the percentage of 32.56%. (2) Teacher counselor revealed the personal experiences of students to the problems being faced in the category very well with the percentage of 41.86%. (3) Teacher counselor brought positive idea of learners was in the good category with the percentage 58.14%. Based on the results above, the researcher suggested that a teacher counselor should care in shaping studentsâ good behavior.